Surface Enhancement and Structure Formation of Metakaolin from Thailand Kaolin on the Various Calcination Temperature - Tanwongwan, Worapak; Wongkitikun, Thanapat; Onpecht, Kobchai; Srilai, Suphada; Assabumrungrat, Suttichai; Chollacoop, Nuwong; Eiad-Ua, Apiluck (My University, 2020)
The metakaolin was chosen as a starting material for the synthesis of the zeolite because it is high crystallinity, reactivity and purity of raw material. Kaolin from Thailand which was selected from 3 different sources including Ratchaburi, Lampang, and Uttaradit were using as starting materials for synthesis of metakaolin by calcination temperature of this study were chosen in the range of 500 to 1000 °C for 2 h. Calcination temperature is significantly affect crystalline size, function group, and configuration of metakaolin by the results which obtained from X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, and scanning electron microscopy techniques were indicated that the best metakaolin was obtained from Uttaradit's kaolin which was calcined at 1000 oC for 2h by it shows the lowest impurities.
Keywords: Calcination temperature; Kaolin; Metakaolin